2021
DOI: 10.4067/s0718-07642021000600053
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades reológicas de quinua (Chenopodium quinoa Wild) obtenidas mediante molienda abrasiva y tratamiento térmico

Abstract: El objetivo de esta investigación fue determinar el efecto de la molienda abrasiva y el tratamiento térmico sobre las propiedades reológicas de harinas de quinua. Se determinó que la molienda abrasiva era apropiada para obtener harinas del germen y del perisperma, pero el tratamiento térmico modificó las propiedades reológicas. El modelo de la potencia fue empleado para determinar el índice de flujo (n) y la consistencia (k). Los resultados evidenciaron diferencias significativas entre el índice n de las harin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The dry milling process is the repetitive steps of crushing, sieving, separating, and grinding to extract the endosperm from the grain by physical methods to obtain a hiper-protein quinoa flour (HPQF) at a low cost and reduced environmental impact (Reichert and Youngs, 1976;Caperuto et al, 2001;Avila Ruiz et al, 2016;D'Amico et al, 2019;Roa et al, 2019). Structural, rheological, and functional properties have been studied (Haros, 2017;Roa-Acosta et al, 2020;Polo et al, 2021) and have shown potential to be included in foods.…”
Section: Introductionmentioning
confidence: 99%
“…The dry milling process is the repetitive steps of crushing, sieving, separating, and grinding to extract the endosperm from the grain by physical methods to obtain a hiper-protein quinoa flour (HPQF) at a low cost and reduced environmental impact (Reichert and Youngs, 1976;Caperuto et al, 2001;Avila Ruiz et al, 2016;D'Amico et al, 2019;Roa et al, 2019). Structural, rheological, and functional properties have been studied (Haros, 2017;Roa-Acosta et al, 2020;Polo et al, 2021) and have shown potential to be included in foods.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior occurs because, in the gelatinization process, the starch granules break, releasing amylose to the aqueous medium and, on cooling, these amylose chains align, forming networks that form gels or viscous suspensions. 18 The n values for the SIF-WM were reduced to 1.064, exhibiting Newtonian behavior. The Newtonian flow shows that the viscosity is independent of the shear rate.…”
Section: Flow Profile Analysismentioning
confidence: 98%
“…Finally, using the Savistky-Golay function, the data were smoothed in the GraphPad Prism 8.0.1 program (RRID:SCR_002798). 18,19 Flow profile Flow properties were performed according to the methodology of Ref. 18 with modifications.…”
Section: Rheological Analysis Pasting Propertiesmentioning
confidence: 99%
“…Shear rate was increased from 0 to 300 s −1 over 5 min. Average apparent viscosity was determined between 180 and 200 s −1 , avoiding the transition zone because of shear rate (Polo et al, 2021). Flow curves (shear stress vs. shear rate) were obtained and fitted to the power law model (Equation 1).…”
Section: Flow Propertiesmentioning
confidence: 99%
“…To determine the pasting properties, the rheometer was programmed to run temperature sweeps consisting of heating (25-90 • C), tempering (90 • C for 5 min), and cooling (90-25 • C) steps at 10 • C/min. Viscosity peak, breakdown (BD) viscosity, and set back (SB) viscosity were recorded in duplicate (Polo et al, 2021).…”
Section: Viscosity Profilementioning
confidence: 99%